Trends in the proportion of women as reviewers, editors, and editorial board members of 15 North American and British medical journals from 2014 to 2019: A retrospective study - Roxanna Wang; Robin Roberts; James C Fredenburgh; Mary Cushman; Jeffrey I Weitz (European Science Editing)
Background and objective: There is persistent men-dominated gender disparity in medical academia. Predominance of men in the editorial makeup of medical journals might contribute to this inequity. This retrospective study (2014–2019)sought to evaluate gender representation in reviewers, editors, and members of the editorial boards in 15 leading medical journals from the United States, Canada, and the United Kingdom.Methods: We surveyed lists of reviewers, editors, and editorial board members from seven journals of internal medicine, a specialty dominated by men; three journals of obstetrics and gynaecology and two of paediatrics, specialties dominated by women; and three journals of psychiatry, a gender-balanced specialty. Information from publicly available resources was used to infer gender, and the percentages of women were calculated. Trends over time were characterized by changes in these percentages from year to year through the linear regression line fitted to the data for each journal.Results: Journals of women-dominated specialties had significantly higher proportions of women reviewers than those of men-dominated or gender-balanced specialties, with mean percentages (95% confidence interval) of 45.8% (40.5%–51.1%), 28.0% (22.3%–33.7%), and 33.8% (27.6%–40.1%), respectively (p <0.001). The proportion of women editors and editorial board members showed no statistically significant differences across the three specialties, and the percentage of women reviewers, editors, and editorial board members increased only slightly over time.Conclusion: These results suggest that the fifteen journals are yet to achieve gender parity in their reviewers, editors, and editorial board members, and continued efforts are needed to achieve gender balance in those three groups of medical academia.